2018
DOI: 10.3390/su10124724
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stakeholders-Oriented Behavior on the Performance of Sustainable Business

Abstract: This study focuses on stakeholder-oriented behavior, throughout organizational culture and organizational behavior, and its effects on the performance of sustainable organizations managed according to Corporative Social Responsibility (CSR) criteria. The investigation demonstrates that the sustainability efforts of a wide range of stakeholders exert various effects on business performance. This investigation tests two integrated conceptual models: (a) Stakeholder Orientation Model estimates the relationships a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 137 publications
(329 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, the involvement of citizens in public decision -making processes and activities is important for strengthening public confidence in the state and confidence is a factor which expresses participation. Therefore, it may be concluded that stakeholder orientation is an essential factor for performance improvement [15]. For that, it is a process of active learning of citizens about democracy that results in understanding of the interactions between institutions in a democratic society on the part of citizens, getting them interested in being a representative of local bodies themselves or giving them the skills to control and oversee citizen representatives.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the involvement of citizens in public decision -making processes and activities is important for strengthening public confidence in the state and confidence is a factor which expresses participation. Therefore, it may be concluded that stakeholder orientation is an essential factor for performance improvement [15]. For that, it is a process of active learning of citizens about democracy that results in understanding of the interactions between institutions in a democratic society on the part of citizens, getting them interested in being a representative of local bodies themselves or giving them the skills to control and oversee citizen representatives.…”
Section: Discussionmentioning
confidence: 99%
“…(2008) in their review of stakeholder theory also found that stakeholder view alignment is essential for effective organisational functioning. Ferro-Soto et al. (2018) concluded that managing organisation from stakeholder's viewpoints can improve financial performance and market performance.…”
Section: Theoretical Background and Hypotheses Framingmentioning
confidence: 99%
“…Organizational management implies a system of values and beliefs, interactions and relationships within the organization [10], focused on stakeholders aims to obtain financial performance and reputation results through an appropriate organizational culture [45], considering management procedures and behaviors as tools to strengthen it. An efficient organizational management system allows communicating the importance and reinforces a behavior for innovation [14] and focuses on the environment [9,46], which is a reflection of the development that the organization can have in intangible aspects since it favors the development of technological innovation and process capabilities, which can lead to a superior performance of the company [42], The factors identified within the context of organizational management are listed in Table 3.…”
Section: Organizational Managementmentioning
confidence: 99%